Advantages of the corporate model of the state sector of the economy of Russia - V. V. Kurchenkov (Real Economics Publishing House, 2018)
At present, the share of the public sector in the Russian economy plays a significant role. The state sector is actively used as a means of regulation to achieve many state social and economic goals, including provision of the stable development of important strategic sectors. The article reveals the features of the formation and development of the corporate model of the public sector of the Russian economy, related, including the creation and functioning of the institution of state corporations. Special features of the formation of the corporate model of the public sector of the Russian economy are identified, by defining its features, principles, advantages and disadvantages of use, including the achievement of the integration effect in the process of interaction of its economic entities. The results could be used in the activities of state structures in the implementation of state policy for the development of the public sector, solving problems of accounting for its boundaries and scales, and in developing and improving strategies for the development of state corporations, and improving the efficiency of their activities.